Molecular and Cellular Analyses of Breast Cancers in Real Life - Castaneda-Altamirano, CA (2022)
Breast cancer is the most common women’s malignancy. Incorporation of biomarkers of prognosis and prediction of response are needed to improve treatment management. Lectures for immunohistochemistry of estrogen, progesterone, and HER2 receptors as well as Ki67 staining in cancer cells have been incorporated, and their positive cutoffs have periodically been reviewed. Gene expression platforms in tumor lesions as well as germline and somatic mutations have also been included in the practice for treatment selection. Liquid biopsy evaluating circulating tumor cells (CTCs) and circulating DNA can also predict survival and has reached the clinical practice, although it needs better standardization. On the other side, biomarkers can also evaluate stroma cells in the tumor microenvironment, and they can predict survival and response to chemotherapy and targeted treatment. They have been incorporated in the daily practice, and new methodologies for obtaining more information are currently being developed.